Solar and Space Weather Radiophysics Current Status and Future Developments - Gary, D.E.; Keller, C.U.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
This volume is the outgrowth of several international meetings to discuss a vision for the future of solar radio physics: the development of a new radio instrument. From these discussions, the concept for the Frequency Agile Solar Radiotelescope (FASR) was born. Most of the chapters of this book are based oninvitedtalksattheFASRScienceWorkshop,heldinGreenbank,WVinMay 2002, and a special session on Solar and Space Weather Radiophysics held at the 200th American Astronomical Society meeting held in Albuquerque, NM in June 2002. Although many of the chapters deal with topics of interest in planning for FASR, other topics in Solar and Space Weather Radiophysics, such as solar radar and interplanetary scintillation, are covered to round out the discipline. The authors have been asked to write with a tutorial approach, to make the book useful to graduate students and scientists new to radio physics. This book is more than a compilation of FASR science topics. The FASR instrument concept is so revolutionary—by extending capability by an order of magnitude in several dimensions at once (frequency coverage, spatial reso- tion,dynamicrange,timeresolution,polarizationprecision)—thatitchallenges scientiststothinkinnewways. Theauthorsofthefollowingchaptershavebeen taskednotonlywithreviewingthecurrentstateofthe?eld,butalsowithlooking to the future and imagining what is possible. Radio emission is extremely complex because it is generated so readily, and every imaginable plasma parameter affects it. This is both its great strength and its weakness.
Solar and Solar Radio Effects on Technologies -- Overview of Solar Radio Physics and Interplanetary Disturbances -- The Frequency Agile Solar Radiotelescope -- Radio Spectral Diagnostics -- Coronal Magnetic Field Measurements Through Gyroresonance Emission -- Coronal Magnetic Field Measurements Through Bremsstrahlung Emission -- Coronal Magnetic Field Measurements Through Quasi-Transverse Propagation -- Overview of Solar Flares -- Electron Transport During Solar Flares -- Decimeter Burst Emission and Particle Acceleration -- Radio Observations of Coronal Mass Ejections -- Tomographic 3D-Modeling of the Solar Corona with FASR -- Coronal Diagnostics with Coordinated Radio and EUV/Soft X-Ray Observations -- Radio Observations of the Quiet Sun -- Interplanetary Radio Bursts -- Solar Radar -- Three-Dimensional Tomography of Interplanetary Disturbances.
Keywords: Space sciences; Observations, Astronomical; Astronomy—Observations.; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Astronomy, Observations and Techniques